1993
DOI: 10.1111/j.1600-0447.1993.tb03420.x
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of an open referral system to a community mental health service

Abstract: The first 590 patients referred to a community mental health service (the Early Intervention Service) in an inner-city district were separated into groups based on their referral source. The service has an open referral system allowing any agency (including patients) to contact the service by letter or by telephone, and priority is given to patients with serious mental illness. The results of open referral showed that the number of referrals was adequate for the service to process, the proportion of inappropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…A previous randomized controlled study found that patients referred to the EIS showed greater improvement in symptoms and were more satisfied with the service than those in a hospitalbased service (12), and that this was achieved at 43% of the cost of the traditional service (13). A further study concluded that an open referral system such as the EIS was likely to be more sensitive to need and to have some advantage over closed referral arrangements in inner-city areas (14). This study showed that the most severely ill patients referred to the service were not referred by general practitioners or psychiatrists but by other agencies.…”
Section: Discussionmentioning
confidence: 81%
“…A previous randomized controlled study found that patients referred to the EIS showed greater improvement in symptoms and were more satisfied with the service than those in a hospitalbased service (12), and that this was achieved at 43% of the cost of the traditional service (13). A further study concluded that an open referral system such as the EIS was likely to be more sensitive to need and to have some advantage over closed referral arrangements in inner-city areas (14). This study showed that the most severely ill patients referred to the service were not referred by general practitioners or psychiatrists but by other agencies.…”
Section: Discussionmentioning
confidence: 81%
“…This is a matter of further investigation. An interesting study by Marriott et a1 (23), investigating the introduction of an open referral system, showed that GPs and other doctors made as many inappropriate referrals as other referral sources, including patient self-referrals, and that patients with a severe illness to a significantly greater extent were referred from other sources than the GP. This shows that setting priorities of the psychiatric services and directing resources towards patients with severe illness is more complicated and affected by a number of other variables than the mode of referral.…”
Section: Discussionmentioning
confidence: 99%
“…Providing a single point of access improves service accessibility (Onyett et al 1994) and ensures referrals are jointly considered for both health and social care provision (Newton et al 1996). Open referral systems have been found to be effective in increasing accessibility of services to the most severely ill people (Marriott et al 1993), although rigorous application of eligibility criteria becomes particularly important when referrals are accepted from a wide range of sources (Onyett et al 1994). This may particularly challenge professionals used to accepting and offering interventions to all new referrals (Newton et al 1996).…”
Section: Introductionmentioning
confidence: 99%